2019
DOI: 10.3802/jgo.2019.30.e8
|View full text |Cite
|
Sign up to set email alerts
|

A novel prediction score for predicting the baseline risk of recurrence of stage I–II endometrial carcinoma

Abstract: ObjectiveTo develop and validate a 3-year recurrence prediction score (RPS) system for predicting the baseline risk of recurrence of stage I–II endometrial carcinoma.MethodsWe reviewed 427 patients with International Federation of Gynecology and Obstetrics staging I–II endometrial carcinoma underwent surgery without any adjuvant therapy from 2005 to 2013. The patients were divided into 2 groups: the test cohort (n=251) comprising those who underwent surgery in odd-numbered years, and the validation cohort (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…As expected in related research, the higher grade, worse pathological type, deeper MI, and positive cervical stromal involvement have been identified to be significantly correlated with poor prognosis. 5,24,25 Establishment of postoperative adjuvant treatment is based on the individual aggressive factors. 26,27 Therefore, influenced by other high-risk factors the hazard ratio suggested that adjuvant therapy may be an invasive factor in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected in related research, the higher grade, worse pathological type, deeper MI, and positive cervical stromal involvement have been identified to be significantly correlated with poor prognosis. 5,24,25 Establishment of postoperative adjuvant treatment is based on the individual aggressive factors. 26,27 Therefore, influenced by other high-risk factors the hazard ratio suggested that adjuvant therapy may be an invasive factor in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were undertaken before hold that the tumor stage, histological grade, pathological type, depth of myometrial invasion, and lymphovascular space involvement are high-risk predictors for relapes. [3][4][5][6] Nevertheless, traditional clinical parameters seem to be not enough to accurately predict the prognosis, 7 especially for J Surg Oncol. 2020;122:1808-1814. wileyonlinelibrary.com/journal/jso 1808 | © 2020 Wiley Periodicals LLC Mingzhu Jia and Peng Jiang contributed equally to the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though only four factors were included in this model, other factors, such as histological grade, depth of myometrial invasion, cervical stromal infiltration, Ki67, or PR, have been shownto have prognostic importance in EC. 4,5,19 According to the risk ratio of the univariate analysis, it seemed that EC was more likely to relapse in patients who had received adjuvant therapy. This could have been confounded by adjuvant therapy being administered to patients at late stages or other high-risk factors for recurrence, which caused adjuvant therapy as a prognostic factor to have strong "collinearity" on univariate analysis, 20 and the "protective effect" of adjuvant therapy may not be adequate to offset the risk raised by these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current models for predicting recurrence in EC are based on classical clinicopathological parameters. 5 The most recent study by Ouldamer et al developed a nomogram model based on age, International Federation of Gynecology and Obstetrics (FIGO) stage, histological type and grade, lymphovascular space invasion, and surgical nodal staging to predict prognosis of patients with stages I-III EC with good discrimination. 4 Immunohistochemical markers have been widely applied in pathological reports, and have already became an important indicator for prognosis in EC and other tumors.…”
Section: Introductionmentioning
confidence: 99%